2023
DOI: 10.1002/nag.3501
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐form solution of fluid flow in and around a crack disk embedded in a 3D porous medium

Abstract: This paper considers the fluid flow through a porous medium containing intersecting fractures and presents three main analytical findings, namely: (1) mass exchange between fractures and surrounding matrix at the fracture intersection;(2) fluid potential solution (pressure field) within the whole domain under the form of a single singular integral equation; and (3) closed-form solutions of fluid flow in and around a crack disc under a far field pressure gradient. The crack is represented mathematically by a 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Scholars have investigated the relationship between hydraulic aperture ( e h ) and mechanical aperture (em${e}_m$) to quantitatively analyze flow characteristics in stressed fractures, 7–9 and eh/em${e}_h/{e}_m$ is collectively referred to as the aperture ratio for simplicity. It has been confirmed that the non‐linear flow behavior in rough fractures, the contact within fractures, and the staggered distribution of porosity lead to a non‐uniform distribution of the flow field 10–13 . The outcomes demonstrate that the nonlinear seepage behavior of fractured rock mass arises from the complex geometric and hydraulic properties of fractures, such as roughness, tortuosity, and heterogeneity, and the coupling effect between fluid flow and rock mass deformation 14–16 .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Scholars have investigated the relationship between hydraulic aperture ( e h ) and mechanical aperture (em${e}_m$) to quantitatively analyze flow characteristics in stressed fractures, 7–9 and eh/em${e}_h/{e}_m$ is collectively referred to as the aperture ratio for simplicity. It has been confirmed that the non‐linear flow behavior in rough fractures, the contact within fractures, and the staggered distribution of porosity lead to a non‐uniform distribution of the flow field 10–13 . The outcomes demonstrate that the nonlinear seepage behavior of fractured rock mass arises from the complex geometric and hydraulic properties of fractures, such as roughness, tortuosity, and heterogeneity, and the coupling effect between fluid flow and rock mass deformation 14–16 .…”
Section: Introductionmentioning
confidence: 74%
“…In this study, a key parameter for evaluating the heat transfer through rock fractures is the fluid temperature at the fracture exit. All parameters are calculated in integral forms, such as Equations ( 11)- (13). 45…”
Section: ℎ = 𝑄 𝐴mentioning
confidence: 99%
See 1 more Smart Citation